Research progress on iron absorption, transport, and molecular regulation strategy in plants - Ning, Xinyi; Lin, Mengfei; Huang, Guohua; Mao, Jipeng; Gao, Zhu; Wang, Xiaoling (Frontiers in Plant Science, 2023)
Iron is a trace element essential for normal plant life activities and is involved in various metabolic pathways such as chlorophyll synthesis, photosynthesis, and respiration. Although iron is highly abundant in the earth’s crust, the amount that can be absorbed and utilized by plants is very low. Therefore, plants have developed a series of systems for absorption, transport, and utilization in the course of long-term evolution. This review focuses on the ﬁndings of current studies of the Fe2+ absorption mechanism Ⅰ, Fe3+ chelate absorption mechanism Ⅱ and plant-microbial interaction iron absorption mechanism, particularly effective measures for artificially regulating plant iron absorption and transportation to promote plant growth and development. According to the available literature, the beneficial effects of using microbial fertilizers as iron fertilizers are promising but further evidence of the interaction mechanism between microorganisms and plants is required.